Schiff Base Derivatives as Carbonic Anhydrases and Cholinesterases Inhibitors: Molecular Docking and Anticancer Studies - Koksal, Zeynep; Guller, Pinar; Sagir, Fatma; Unlu, Seda; Elmali, Fikriye Tuncel (WILEY, 2026)
This study investigated the inhibitory effects of a series of Schiff base derivatives, designated S1-S4, on human carbonic anhydrase isoenzymes (hCA I and hCA II), acetylcholinesterase (AChE), and butyrylcholinesterase (BuChE) through in vitro and in silico analyses. Among the evaluated compounds, S3 emerged as the most potent multi-target inhibitor, demonstrating strong competitive inhibition of AChE (IC50 = 12.88 +/- 5.30 nM; K-i = 7.55 +/- 2.60 nM) and BuChE (IC50 = 13.96 +/- 2.02 nM; K-i = 13.00 +/- 6.80 nM). Furthermore, the compounds exhibited notable inhibitory activity against human carbonic anhydrase isoforms, with S3 inhibiting hCA I (IC50 = 7.90 +/- 2.50 nM; K-i = 14.0 +/- 6.70 nM, non-competitive) and hCA II (IC50 = 23.00 +/- 9.74 nM; K-i = 10.20 +/- 3.20 nM, competitive). While the binding affinities of the Schiff bases for the AChE receptor were predicted to be lower than that of Tacrine, the binding affinities of S2 and S4 for BuChE were estimated to be higher. For hCA I, the estimated binding energy of S1 was lower than that of acetazolamide, and for hCA II, the estimated binding energy of S2 was determined to be lower than that of acetazolamide. The cytotoxicity of the compounds was assessed against the aggressive PC3 prostate cancer cell line. Compound S4 emerged as the most potent cytotoxic agent, with a statistically significant IC50 value of 10.88 mu M. Molecular docking studies corroborated the experimental findings, providing valuable insights into the underlying mechanisms of action. In conclusion, the objective of this study was to investigate the enzyme inhibitory and anticancer potential of synthesized Schiff bases using molecular docking analyses. The results indicate that compounds S3 and S4 exhibit strong inhibitory activity and may represent promising candidates for the development of novel therapeutic agents.
Keywords: anticancer; carbonic anhydrases; cholinesterases; inhibition; molecular docking; Schiff base; K-I; ACETYLCHOLINESTERASE; BUTYRYLCHOLINESTERASE; COMPLEXES; IC50; Biochemistry & Molecular Biology; Toxicology